PERTANGGUNGJAWABAN DAN AKIBAT HUKUM PERSEROAN TERBATAS TERKAIT BENEFICIAL OWNERSHIP - Glen Yehezkiel Hariara; Christin Septina Basani (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
As the modern business world develops, share ownership in Limited Liability Companies is not listed in the shareholder register. Shareholders can appoint someone to act on behalf of the beneficial owner or what is usually called beneficial ownership. The application of beneficial ownership in this Limited Liability Company is high risk. This could result in criminal acts being committed by the beneficial owner, such as money laundering, terrorism financing and tax evasion without being identified. The issuance of Presidential Regulation No. 13 of 2018 concerning the Implementation of the Principle of Recognizing the Beneficial Owners of Corporations in the Context of Preventing and Eradicating Crimes of Money Laundering and Terrorism Financing Crimes gives rise to new principles. This research is a normative juridical analysis, namely a legal research method that focuses on the study of legal norms, statutory regulations and other written legal documents. The data used is in the form of journals or legal writings. The conclusion reached by the author regarding the responsibility received by the beneficial ownership is that they are subject to criminal sanctions for committing criminal acts using a Limited Liability Company and can be sued for compensation if the beneficial ownership’s actions are detrimental to the Limited Liability Company and the legal consequences that will be received by the Limited Liability Company are blocking access. where a Limited Liability Company cannot make changes to its articles of association and change business data.